Using hiPSC‐CMs to Examine Mechanisms of Catecholaminergic Polymorphic Ventricular Tachycardia. Issue 12 (27th December 2021) - Arslanova, Alia; Shafaattalab, Sanam; Ye, Kevin; Asghari, Parisa; Lin, Lisa; Kim, BaRun; Roston, Thomas M.; Hove‐Madsen, Leif; Van Petegem, Filip; Sanatani, Shubhayan; Moore, Edwin; Lynn, Francis; et al.
Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a potentially lethal inherited cardiac arrhythmia condition, triggered by physical or acute emotional stress, that predominantly expresses early in life. Gain‐of‐function mutations in the cardiac ryanodine receptor gene ( RYR2 ) account for the majority of CPVT cases, causing substantial disruption of intracellular calcium (Ca 2+ ) homeostasis particularly during the periods of β‐adrenergic receptor stimulation. However, the highly variable penetrance, patient outcomes, and drug responses observed in clinical practice remain unexplained, even for patients with well‐established founder RyR2 mutations. Therefore, investigation of the electrophysiological consequences of CPVT‐causing RyR2 mutations is crucial to better understand the pathophysiology of the disease. The development of strategies for reprogramming human somatic cells to human induced pluripotent stem cells (hiPSCs) has provided a unique opportunity to study inherited arrhythmias, due to the ability of hiPSCs to differentiate down a cardiac lineage. Employment of genome editing enables generation of disease‐specific cell lines from healthy and diseased patient‐derived hiPSCs, which subsequently can be differentiated into cardiomyocytes. This paper describes the means for establishing an hiPSC‐based model of CPVT in order to recapitulate the disease phenotype in vitro and investigate underlying pathophysiological mechanisms. The framework of this approach has the potential to contribute to disease modeling and personalized medicine using hiPSC‐derived cardiomyocytes. © 2021 Wiley Periodicals LLC.